Transcriptome analysis of Enterococcus faecalis in response to alkaline stress - shujun, Ran; bin, Liu; Wei, Jiang; Jingping, Liang (Frontiers in Microbiology, 2015)
E. faecalis is the most commonly isolated species from endodontic failure root canals; its persistence in treated root canals has been attributed to its ability to resist high pH stress. The goal of this study was to characterize the E. faecalis transcriptome and to identify candidate genes for response and resistance to alkaline stress using Illumina HiSeq 2000 sequencing. We found that E. faecalis could survive and form biofilms in a pH 10 environment and that alkaline stress had a great impact on the transcription of many genes in the E. faecalis genome. The transcriptome sequencing results revealed that 613 genes were differentially expressed (DEGs) for E. faecalis grown in pH 10 medium; 211 genes were found to be differentially up-regulated and 402 genes differentially down-regulated. Many of the down-regulated genes found are involved in cell energy production and metabolism and carbohydrate and amino acid metabolism, and the up-regulated genes are mostly related to nucleotide transport and metabolism. The results presented here reveal that cultivation of E. faecalis in alkaline stress has a profound impact on its transcriptome. The observed regulation of genes and pathways revealed that E. faecalis reduced its carbohydrate and amino acid metabolism and increased nucleotide synthesis to adapt and grow in alkaline stress. A number of the regulated genes may be useful candidates for the development of new therapeutic approaches for the treatment of E. faecalis infections.